Rancang Bangun Game Edukasi Dream Academy Berbasis Android - Agus Kerta Nugraha, I Wayan; Agung Cahyawan Wiranatha, Anak Agung Ketut; Agus Dwi Suarjaya, I Made (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 3 No 1 (2022): JITTER, Vol.3, No.1, April 2022DO - 10.24843/JTRTI.2022.v03.i01.p22, 2022)
Educational games are games that contain knowledge or information that is educational. The knowledge is shown in the game and can also be through the game storyline in the application itself. The use of games can keep students motivated and make learning more interesting if it also includes students. But what happens in junior high school lately is that students have difficulty capturing learning materials that have been explained by teachers. Students often forget what has been learned when the teaching and learning process is complete. So that it takes repetition so that the subject matter described can be remembered by students. Overcoming these problems, dream academy educational games were made. Dream Academy game gives players playing the main character whose name can be handpicked as desired and built using the Unity3d Engine with C# programming language applied to Android Smartphones. Dream Academy's educational game uses black box testing as a test of game application action with 12 test cases that get the expected results that are 100% successful, and heuristic evaluation testing uses a method of spreading questionnaires involving 30 respondents with results obtained on average above 120, based on the category of heuristic problem level that is no problem and no need for improvement.